Multi level marketing and the impact on distributors’ loyalty of (un)success factors: an approach to measure loyalty - Grade, Gonçalo Filipe Monteiro (2019)
Multi-level marketing industry besides on the 20th century has had a great expansion and some companies became huge players in their activity sectors, a lot of missing points still exists and remain to be explained. This study has the aim to explore MLM model, making a three-part analysis taking into account the stakeholders of MLM - companies, distributors and consumers. At the same time offering a way to multi-level marketing companies’ managers can accurate the loyalty and the changes in loyalty that distributors have once a decision is taken by them (managers). Using a sample with 149 answers, were tested the factors pointed in literature review having a negative impact towards the distributors’ loyalty. The results discussion and analysis suggest that those “negative” factors for distributors loyalty towards the companies weren’t negative. The empirical results show that they have a positive influence over the distributors loyalty, rejecting almost all hypotheses. The proposed model offers a tool to managers to better understand which the negative and positive factors and those are which have more and less influence over loyalty. Analysing the model, we also can identify differences in factors’ interpretation over the active and non-active distributors.